2008
DOI: 10.1292/jvms.70.1247
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Measurement of the Feline Serum Amyloid A (SAA) Concentration by Human SAA Turbidimetric Immunoassay and Its Clinical Application

Abstract: ABSTRACT. Serum amyloid A (SAA) is one of the major acute phase proteins in cats that has potential to be used as an inflammatory marker. A previous study showed that the human SAA turbidimetric immunoassay (hSAA-TIA) could be used to measure the SAA concentration in cats. The objectives of the present study were to assess use of hSAA-TIA for determining the feline SAA concentration and to evaluate its clinical application. Recombinant feline SAA protein (rfSAA) was expressed in Escherichia coli and purified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
73
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 32 publications
4
73
1
Order By: Relevance
“…c, 14 The reference range of feline SAA was selected as ≤0.82 mg/l on the basis of a previous study. 14 Cats were divided into 2 groups according to SAA concentration.…”
mentioning
confidence: 99%
“…c, 14 The reference range of feline SAA was selected as ≤0.82 mg/l on the basis of a previous study. 14 Cats were divided into 2 groups according to SAA concentration.…”
mentioning
confidence: 99%
“…Measurement of SAA and AGP concentrations are considered useful in detecting the presence of inflammation (17,26,27). In addition, AGP in cat serum or effusion samples is a recognised biomarker of FIP (6,21,25).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of SAA concentration (29.4 -88.3 mg/L) in FIP was clinically valuable to detect the infl ammatory process in affected cats [54] and a 10-fold increase has been found, suggesting its potential as a biomarker of this disease [15]. Moreover, a study suggested that the median survival time of cats with elevated SAA levels (>0.82 mg/L) was signifi cantly shorter in various diseases, including FIP [8].…”
Section: Catsmentioning
confidence: 99%